A Filosofia da História de Danto em retrospectiva - Ankersmit, Frank; Mioto, Júlio César; Menezes, Jonathan (Revista de Teoria da História, 2025)
Tradução de: ANKERSMIT, Frank. Danto’s Philosophy of History in Retrospective. In: DANTO, Arthur C. Narration and Knowledge. New York: Columbia University Press, 2007. p. 364-393.